Features of the petroleum products pricing in Russia, in the USA, and Saudi Arabia. (November 2020) - Provornaya, I.V.; Filimonova, I.V.; Nemov, V.Yu.; Komarova, A.V.; Dzyuba, Y.A.
Abstract: The most important reason for the development of the world energy market is the sustainable increase in energy production and consumption. Environmental factors and inter-fuel competition influence the structure of the market. Such factors as the emergence of new types of energy and the development of technologies for hard-to-recover reserves production also have a strong influence on the stability of the global energy industry. However, in the long-term perspective, fossil fuels will remain the most important source of energy, especially in production countries. An exception may be only some regional markets. The consumption of oil and oil products continues to have a significant share in the transport sector and, due to the forecast of leading energy organizations, it will continue to take a large share in the structure of energy consumption of transport for the next twenty years. Thus, the study of the specifics of pricing for oil and oil products is an urgent issue in the current realities. In this article, the authors evaluated the impact of main influencing factors on oil products' prices in the three largest oil-producing and exporting countries in the world: Russia, the United States, and Saudi Arabia. Based on a retrospective study of prices for petroleum products, significant factors have been identified to determine the peculiarities of the structure of prices for petroleum products in different countries. The authors have established the patterns of pricing in the analyzed market, arising due to the different levels of economic development of the countries under analysis, differences in taxation systems of the analyzed industry, and different rates of depletion of hydrocarbon reserves. The authors used the systematization and ordering of data in tabular and graphical form to identify stable patterns and trends in the pricing of petroleum products in the context of the key oil-producing countries. According to this research, we can conclude that: the main factor affecting the cost structure of gasoline in 2010-2018 in Russia is the tax burden, which currently accounts for 62.8 % of the oil product's cost; the price of petroleum products in the United States is dependent on the cost of oil production; and the prices of oil products in the domestic market of Saudi Arabia currently depend on the cost of oil production and refining costs.